Interpretasi Makna Ruang Arsitektur Joglo Bucu di Ponorogo - Roosandriantini, Josephine; Handayani Asriningpuri; James Efandaru; Odo Grean Kaesar Putra Wardhana (Nature: National Academic Journal of Architecture, 2024)
The existence of Javanese architecture is an architectural figure that is present in Javanese cultured society, and from generation to generation and has meaning both symbolically and architecturally. Javanese architecture is not just a building, but a physical form that has symbols, architectural details that contain interpretations of meaning in them. The issue of this research arises in relation to Javanese architecture in Ponorogo, namely the Joglo Bucu architecture (a type of Javanese house in Ponorogo) which has different height proportions from Joglo in general and has transformed into a more modern one in terms of materials, namely on the side (wall) enclosures. . This research aims to understand that architecture is a relationship between form, function and meaning, starting from the top (roof), side (walls) and bottom (floor). This research method uses a qualitative descriptive method which is more about interpreting the meaning of the Joglo Bucu architectural space in Ponorogo with its architectural elements, namely Griya Ngajeng, Griya Wingking, Pawon. The results of this research are that the Interpretation of the Meaning of the Joglo Bucu Architectural Space in Ponorogo is that it can show a house with upper middle social status, because it has a wingking house and a ngajeng house. Joglo Bucu also has a pawon which only has functional meaning. It can be developed in further research that Ponorogo traditional houses have differences, namely the structure and typology of each region.